The poorest and hungry: Assessments, analyses, and actions - von Braun, Joachim; Hill, Ruth Vargas; Pandya-Lorch, Rajul (International Food Policy Research Institute, 2009)
Although many millions of people have exited poverty in recent decades, much of the reduction in poverty has benefited people living close to the poverty line rather than those at the very bottom of the income distribution. This book is not focused on poverty per se but rather is focused on looking particularly at those most deprived in society. It is this focus on the poorest and hungry people that is the major contribution of this volume. Relatively little is known about people living in extreme deprivation. Who are the poorest of the poor and those most afflicted by hunger? Who are those who are left behind or out of poverty and hunger reduction processes? Why is poverty so persistent in some places and among some people? What are the key pathways out of ultra poverty and hunger? Which strategies, policies, and interventions have been successful in eradicating ultra poverty and hunger so far? In addition, the book features essays by leading policymakers and practitioners who share their views on these key issues and thereby contribute to the diversity of perspectives presented. This edited book seeks to lay out the major issues involved in realizing improvements in the welfare of the world’s poorest people. It is not designed to be read at one sitting; rather it is a “recipe book” for use by policymakers and practitioners as a guide to approaches and options as well as by academics and researchers as an instrument for training and teaching purposes. To enable this material to be accessible to a wide audience, we deliberately asked the authors to refrain from adding references in the text but instead to direct readers interested in fuller discussions and more data to the further readings referenced at the end of each chapter